Fluorometric Detection of Al3+ Ion in Mixed Aqueous Solvent Based on Simple Schiff-Base Molecular Prob - Das, Sanju (Asian Journal of Chemistry, 2023)
A simple fluorometric detection for Al3+ ion in mixed aqueous medium using a simple Schiff-base molecule through PET mechanism is discussed. The di-phenolic Schiff-base molecule (EAMHM) was synthesized by the condensation reaction of multiple phenolic aldehyde molecules with a diamine containing multiple aldehyde-reacting primary amine moieties. The extremely low fluorescence quantum yield for EAMHM is highly useful for the off-mode of fluorescence sensing purposes. Contrary to various other cations Ni2+, Mg2+, Co2+, Cu2+, Zn2+, Cr3+, Cd2+, Fe3+, Ba2+, Hg2+, the selective Al3+ ion induced large fluorescence enhancement can be employed to detect Al3+ even in the presence other bi- or tri-valent cations. Moreover, linear change in fluorescence intensity with Al3+ concentration is highly beneficial for ratiometric detection of unknown Al3+ concentrations. As revealed from various spectroscopic and theoretical calculations, EAMHM forms a 1:1 complex with Al3+ showing a large increase in fluorescence intensity. It has also been identified that efficient photo-induced electron transfer (PET) in free EAMHM is mainly responsible for its low fluorescence intensity, whereas the removal of such PET process during its complexation with Al3+ produces large fluorescence enhancement. The structural and electronic parameters of the free EAMHM and EAMHM-Al3+ complex have been analyzed using DFT-based theoretical calculations.